Metacognitive Awareness of Young EFL Learners: A Case Study on Two Siblings - Suci Mulyani; Istanti Hermagustiana; Syamdianita Syamdianita (Yayasan Visi Intan Permata, 2025)
This study aims to explore how two young EFL learners who are siblings demonstrate metacognitive awareness. A case study design was employed, incorporating interviews, observation checklists, and field notes to gather data. The participants were two young EFL learners studying in a private course. The older learner (FZ) is 12 years old and is a seventh-grade student, while the younger one (GV) is 10 years old and is in the fifth grade. Data was analyzed using thematic analysis. Results found that both students demonstrated metacognitive knowledge in declarative, procedural, and conditional types. In metacognitive regulation, the types that mainly occurred were monitoring, debugging, and evaluating. Findings declared that both participants demonstrated metacognitive awareness in EFL learning, including metacognitive knowledge (declarative, procedural, and conditional) and regulation (monitoring, debugging, and evaluation). Despite some shared patternsparticularly in metacognitive knowledgethe older learner showed more structured, reasonable, and consistent patterns in the overall awareness, while the younger learner showed more spontaneous and reactive patterns.